Quelles compétences émotionnelles protègent des différentes dimensions du burnout chez les enseignants du primaire ? - Philippe Gay; Philippe A. Genoud (Nantes Université, 2020)
Emotional competences refer to a wide range of knowledge, skills and dispositions (e.g., identifying, understanding, expressing, listening, using and regulating emotions) that can be divided into two categories: intrapersonal and interpersonal skills (Brewer et al., 2013). Good emotional skills contribute to better mental and physical health, more satisfying social and marital relationships and greater professional success. This research examines the relationships between the 10 emotional subskills (five intrapersonal, five interpersonal) assessed by the Brasseur et al. questionnaire and the teachers' burnout level as assessed on the three dimensions proposed by Maslach and Jackson (1986): emotional exhaustion, depersonalization and reduced personal achievement. The results obtained in a sample of 164 primary school teachers (M-age = 40.32[±11.85], 85% female) show significant low to moderate correlations between at least one emotional competence and each dimension of burnout. Regression analyses specify that there are essentially better intrapersonal skills (particularly the understanding of emotions) that are associated with lower levels of burnout on the dimensions of depersonalization and loss of personal achievement. In the light of these analyses, tailor-made training courses are mentioned to promote the development of specific emotional skills among teachers in the prevention of various problems associated with burnout and classroom management.